Sistem Pemilihan Karyawan Baru Dengan Menggunakan Metode Topsis di PT Tri Adi Bersama (Anteraja) - Wibowo, Bagus Yustiraju; Sonny, Michael (Yayasan Bina Internusa Mabarindo, 2024)
This research focuses on a decision support system for the selection of new employees at PT. Tri Adi Bersama (Anteraja), Jakarta. The method used in this study is the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The main issues identified in this research include a selection process that is still conducted manually, a lack of precision and fairness in selection, and insufficient integrated data and in-depth analysis. By using software tools, the company can more easily determine the best candidates for hiring, and information on hiring decisions is stored in a MySQL DBMS, accessible at any time. This decision support system integrates information technology with practical needs to support the effective management of employee recruitment. The system objectively and transparently evaluates the company’s candidate proposals through data analysis and predefined criteria. It uses the TOPSIS approach to ensure that decisions can be measured within a specific time frame.